2017
DOI: 10.1155/2017/9645874
|View full text |Cite
|
Sign up to set email alerts
|

Role of MicroRNA-103a Targeting ADAM10 in Abdominal Aortic Aneurysm

Abstract: MicroRNAs (miRNAs) are deregulated in various vascular ailments including abdominal aortic aneurysm (AAA). MiR-103 is involved in vascular, metabolic, and malignant diseases, but whether it participates in the pathogenesis of AAA remains elusive. ADAM10 plays a vital role in the formation of aneurysm, but whether miRs modulate its activity during AAA formation is totally unknown. In this study, we detected the significantly increased protein expression of ADAM10 in angiotensin II induced murine AAA specimens, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 50 publications
(71 reference statements)
2
25
0
Order By: Relevance
“…22 MiR-103a has been revealed to exert inhibitory effect on AAA growth by targeting ADAM10. 23 Our present study focuses on the role of miR-195 in AAA progression and found that miR-195 was up-regulated in the aortic media of AAA patients, which was consistent with the finding reported by Zampetaki et al 10 However, the potential mechanisms of miR-195 involved in AAA pathology is far from being addressed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…22 MiR-103a has been revealed to exert inhibitory effect on AAA growth by targeting ADAM10. 23 Our present study focuses on the role of miR-195 in AAA progression and found that miR-195 was up-regulated in the aortic media of AAA patients, which was consistent with the finding reported by Zampetaki et al 10 However, the potential mechanisms of miR-195 involved in AAA pathology is far from being addressed.…”
Section: Discussionsupporting
confidence: 92%
“…Ectopic expression of miR‐145 by lentivirus infection apparently reduced the incidence of AAA . MiR‐103a has been revealed to exert inhibitory effect on AAA growth by targeting ADAM10 . Our present study focuses on the role of miR‐195 in AAA progression and found that miR‐195 was up‐regulated in the aortic media of AAA patients, which was consistent with the finding reported by Zampetaki et al .…”
Section: Discussionsupporting
confidence: 91%
“…MiRNAs are non‐coding RNAs, and can mediate cell proliferation, apoptosis and other biological functions by targeting multiple transcription factors . Previous studies have confirmed that ADAM10 was a target of miR‐103a‐3p, and silencing of ADAM10 abated the inflammation of murine abdominal aorta . Moreover, miR‐103a‐3p negatively regulates PTEN expression, leads to the increased expression of immunosuppressive factors in lung cancer cells .…”
Section: Discussionmentioning
confidence: 94%
“…A previous study showed increased promoter activity for an ADAM10 promoter‐luciferase construct compared to an ADAM10 promoter‐luciferase‐3′‐UTR construct in SH‐SY5Y cells, indicating the involvement of miRNAs in the posttranscriptional regulation of ADAM10 . Several miRNAs targeting ADAM10 have been reported in pathological conditions, such as tumours and AD . However, the miRNAs involved in these pathological conditions nearly overlap; hence, the involvement of miRNAs in ADAM10 regulation is most likely disease specific, necessitating the development of disease‐specific strategies for treating ADAM10‐related diseases (Figure ; Table ).…”
Section: Regulatory Mechanisms Of Adam10 Expressionmentioning
confidence: 99%
“…57 Several miRNAs targeting ADAM10 have been reported in pathological conditions, such as tumours and AD. [66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82] However, the miRNAs involved in these pathological conditions nearly overlap; hence, the involvement of miRNAs in ADAM10 regulation is most likely disease specific, necessitating the development of disease-specific strategies for treating ADAM10-related diseases ( Figure 1; Table 1). miRNA/ADAM10 pathways have been primarily defined in tumours and AD but are undetermined in epilepsy.…”
Section: ′-Utr Regulation Of Adam10 Expressionmentioning
confidence: 99%